2019
DOI: 10.1167/iovs.18-25458
|View full text |Cite
|
Sign up to set email alerts
|

Dual Properties of Lactate in Müller Cells: The Effect of GPR81 Activation

Abstract: Citation: Vohra R, Aldana BI, Waagepetersen H, Bergersen LH, Kolko M. Dual properties of lactate in Müller cells: the effect of GPR81 activation. Invest Ophthalmol Vis Sci. 2019;60:999-1008. https://doi.org/ 10.1167/iovs.18-25458PURPOSE. Besides being actively metabolized, lactate may also function as a signaling molecule by activation of the G-protein-coupled receptor 81 (GPR81). Thus, we aimed to characterize the metabolic effects of GPR81 activation in Müller cells.METHOD. Primary Müller cells from mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…While lactate receptor agonists have been tested using several in vitro paradigms (Dvorak et al, 2012;Liu et al, 2012;Bozzo et al, 2013;Lauritzen et al, 2014;Castillo et al, 2015;Herrera-Lopez and Galvan, 2018;Vardjan et al, 2018;de Castro Abrantes et al, 2019;Vohra et al, 2019), their effects have been only recently tested in the central nervous system with unclear results (Lev-Vachnish et al, 2019;Scavuzzo et al, 2020). To further investigate in this direction and shed some light on a presumable dual protective effect of lactate, we tested if HCAR1 stimulation could provide neuroprotection when administered in vivo in a mouse model of transient hypoxiaischemia.…”
Section: Introductionmentioning
confidence: 99%
“…While lactate receptor agonists have been tested using several in vitro paradigms (Dvorak et al, 2012;Liu et al, 2012;Bozzo et al, 2013;Lauritzen et al, 2014;Castillo et al, 2015;Herrera-Lopez and Galvan, 2018;Vardjan et al, 2018;de Castro Abrantes et al, 2019;Vohra et al, 2019), their effects have been only recently tested in the central nervous system with unclear results (Lev-Vachnish et al, 2019;Scavuzzo et al, 2020). To further investigate in this direction and shed some light on a presumable dual protective effect of lactate, we tested if HCAR1 stimulation could provide neuroprotection when administered in vivo in a mouse model of transient hypoxiaischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Various degenerative conditions such as glaucoma and diabetic retinopathy are typically associated with the death of retinal ganglion cells (RGCs). This cell death is prevented by MCs, which have been shown to require lactate for proper function and health [ 19 ]. Evidence has suggested that this lactate consumption is preferential to glucose, and that MCs can even convert lactate to glycogen as a storage mechanism, regulating overall lactate levels in the retina as a whole [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic mapping of [U- 13 C]glucose and [U- 13 C]lactate in the retina using GC-MS was performed as previously described [21][22][23]37,38]. Briefly, retinal extracts were reconstituted in water, acidified to pH 1-2 with HCl, and evaporated to dryness under nitrogen flow.…”
Section: Retinal Explant Incubations With [U-mentioning
confidence: 99%
“…Aerobic glycolysis is the process of glucose breakdown to pyruvate and/or lactate and two ATP molecules that account for 80-96% of total glucose consumption in the retina [19,20]. Both lactate and pyruvate are known retinal energy sources [21][22][23][24][25], which can be further metabolized in the vast number of retinal mitochondria [26,27], where most ATP is produced through oxidative phosphorylation after the tricarboxylic (TCA) cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation